Re B‐S: a glass half full? An exploration of the implications of the Re B‐S judgment on practice in the family courts. Issue 4 (28th August 2014) - Gupta, Anna; Lloyd‐Jones, Edward
Abstract: The family courts in England and Wales are being significantly reformed in line with the coalition government's aim to speed up the process and increase the numbers of children being adopted from care. In September 2013, the Court of Appeal handed down a judgment, R e B ‐ S ( C hildren) [2013] EWCA Civ 1146, that has wide‐ranging implications for professional practice and decision making in care proceedings. The judgment challenges the policy direction and provides guidance about what is required before courts can make orders separating children from their birth families, particularly in cases of non‐consensual adoption. In this paper, we outline the changes occurring in the family justice system, some key elements of R e B ‐ S, and examine the challenges for implementing practice consistent with the requirements of R e B ‐ S . It is argued that the standards set by R e B ‐ S are unlikely to be fully implemented without much further attention to the complexities posed by the policy and practice context of social work with children and their families involved in care proceedings.